Critical Factors Affecting Construction Labor Productivity: A Systematic Review and Meta-Analysis - Feihong Jian; Qian Liu; Cong Feng; Qiaoyi Hu; Qishu Yu; Qi Guo (Buildings)
This study aims to identify and quantify the critical factors influencing construction labor productivity. A systematic review and meta-analysis of 27 empirical studies published between 2000 and 2024 were conducted in accordance with PRISMA guidelines. This study synthesizes findings from a variety of global studies and calculates the relative importance index of various factors affecting construction labor productivity. The findings indicate that 66 CFs, categorized into 12 groups, influence construction labor productivity. The results findings underscore the pivotal role of labor-related factors, particularly “worker experience and skills”, and site management factors, such as “competent supervisors” and “effective communication”. Additionally, environmental factors, such as “weather conditions”, have been demonstrated to play a significant role. The meta-analysis identified substantial regional variations and an increasing importance of factors like worker motivation and technological advancements. Moreover, in light of the evident disparities among regional influential factors, including but not limited to climate, economics, and culture, the findings of this study underscore the imperative for customized, localized management methodologies to enhance construction labor productivity, which will provide practical suggestions for project managers in the region and globally.